The Effectiveness of Powtoon as Creative Educational Media Regarding Early Detection of Pregnancy Risk - Suparni, Suparni; Aisyah, Risqi Dewi; Fatkhudin, Aslam (JURNAL PROTEKSI KESEHATAN, 2024)
Health promotion aims to provide health messages to the public so that they apply healthy living behaviors. It is hoped that the public will have information about health and the prevention of health problems. One way is through health counseling that increases public knowledge and attitudes. This study focused on pregnant women in the Working Area of the Buaran Health Center, Pekalongan, using a simple experimental design with a control group and a simple random sample, involving 30 pregnant women per group. Data were collected through pre- and post-treatment questionnaires in the control group and treatment. Data analysis with the Mann-Whitney test showed a significance value of 0.000 (<0.05) with a confidence interval of 95%. In conclusion, the Powtoon method is more effective than the question and answer lecture in increasing the knowledge of pregnant women about early detection of pregnancy risks. It is recommended to the Health Office to socialize these results to increase the knowledge of pregnant women about pregnancy risk factors.